Potential interference of graphene nanosheets in immune response via disrupting the recognition of HLA-presented KK10 by TCR: a molecular dynamics simulation study. Issue 45 (17th November 2021) - Ye, Rui; Song, Wei; Feng, Mei; Zhou, Ruhong
Abstract : This article demonstrated that graphene nanosheets could disrupt the critical protein–protein interactions between TCR and peptide-HLA and impair the antigen recognition by TCR. Abstract : Graphene and its derivatives have emerged as a promising nanomaterial in biomedical applications. However, their impact on biosafety continues to be a concern in the field, particularly, their potential cytotoxicity to our immune system. In this study, we used all-atom molecular dynamics simulations to investigate the potential interference of graphene nanosheets in antigen presentation and recognition in immune response. For the illustrated human immunodeficiency virus (HIV) antigen peptide KK10, human leukocyte antigen (HLA), and T cell receptor (TCR) ternary complex, we found that the graphene nanosheet could disrupt the critical protein–protein interactions between TCR and peptide-HLA and impair the antigen recognition by TCR, leaving the antigen presentation unaffected. Moreover, the hydrophobic interaction and van der Waals potential energy collectively drive the spontaneous separation of TCR from the peptide-HLA complex by graphene nanosheets. Our findings demonstrated theoretically how the graphene nanosheet could interfere with the immune response and provided useful insights for reducing the risk of graphene-based nanomaterials in biomedical applications.